Mechanism Analysis of Highly Effective Imidazole-Schiff Corrosion Inhibitor on P110 in HCl Solution - LIU Wenchao, WANG Pengjie, TANG Zijie, LI Hao, WANG Ming'an, LIU Wanying, LIN Yuanhua (Cailiao Baohu)
In order to inhibit the corrosion of pipeline steel during oilfield acidification，an imidazole-Schiff corrosion inhibitor (IAP) was synthesized.The corrosion inhibition performance and mechanism of IAP corrosion inhibitor with different concentration on P110 steel in 15%HCl solution were studied through weight loss and electrochemical tests.Subsequently，Fourier infrared spectroscopy (FTIR)，scanning electron microscopy (SEM) ＋energy dispersive spectrometer (EDS) and X-ray photoelectron spectroscopy (XPS) were used to further confirm the inhibition mechanism of IAP on P110 steel in 15%HCl.In addition， the rationality of inhibition mechanism was further clarified from the molecular level by theoretical calculation.Results showed that when IAP added concentration was 400.0 mg/L，the weight loss test corrosion inhibition efficiency of P110 steel in 15%HCl was 97.58%， the test results of AC impedance spectrum (EIS) and potentiodynamic polarization (Tafel)curve showed that the corrosion inhibition efficiencies were 97.32%and 96.76%， respectively.EIS test results proved that IAP played a role in corrosion inhibition by forming film on the surface of P110 steel， and Tafel curve test results proved that IAP was a mixed corrosion inhibitor mainly based on anode inhibition.Meanwhile， the adsorption of IAP on P110 steel followed Langmuir isothermal adsorption equation and could be spontaneously adsorbed on the surface of P110 steel.FTIR，SEM＋EDS，and XPS successfully detected the protective film formed by IAP on the surface of P110 steel.Density functional theory (DFT) and molecular dynamics (MD) proved that the active sites of IAP were benzene ring and imidazole ring.Specifically，the benzene ring could accept excess electrons on the surface of Fe，the lone electron pair of N on the imidazole ring formed a stable coordination bond with Fe， and MD could further proved that IAP were spontaneously adsorbed on the surface of Fe.Overall，IAP corrosion inhibitor could demonstrate excellent corrosion inhibition performance in 15%HCl corrosive medium，with its mechanism involving the formation of a stable protective film on the surface of P110 steel.